Essays on growth and business cycles - Vinci, Francesca R. (2020)
This thesis is comprised of two papers contributing research output to the field of Macroeconomics, focusing on the nexus between growth and business cycles. The first paper represents a theoretical contribution to the literature attempting to shed light on the mechanics behind economic recovery after negative shocks, as well as the role played by policy interventions in such context. The work proposes a model to generate V-shaped and L-shaped recoveries, in line with observed economic dynamics, and discusses the crucial importance of monetary policy interventions in determining the shape of the recovery. The second paper comprises an empirical exercise and aims to contribute to the literature focusing on the rise of the intangible economy. The paper answers two research questions relevant to build a better understanding of the consequences of the structural transformation process towards an economy that relies increasingly on intangible assets for production. First, this work includes an analysis of the role played by different categories of intangible investment for firm performance. Second, it investigates weather the rise of intangible intensity was affected by the Great Recession, contributing novel empirical evidence on the medium to long run effects of recessions.